Polemic and literature surrounding the French wars of religion - Kendrick, Jeff; Maynard, Katherine S. (Studies in medieval and early modern culture, 2019)
Polemic and Literature Surrounding the French Wars of Religion demonstrates that literature and polemic interacted constantly in sixteenth-century France, constructing ideological frameworks that defined the various groups to which individuals belonged and through which they defined their identities. Contributions explore both literary texts (prose, poetry, and theater) and more intentionally polemical texts that fall outside of the traditional literary genres. Engaging the continuous casting and recasting of opposing worldviews, this collection of essays examines literature's use of polemic and polemic's use of literature as seminal intellectual developments stemming from the religious and social turmoil that characterized this period in France